Study of carboxymethyl cellulose from papaya peels as binder in ceramics - Pornchai Rachtanapun (2018)
Effects of carboxymethyl cellulose from papaya peel (CMCp) on the properties of ceramics were investigated. Cellulose was extracted from papaya peels by NaOH and then it was modified by chloro acetic acid to obtain carboxymethyl cellulose. The prepared CMCp was applied as a binder in ceramic slip in order to increase its viscosity. Sodium silicate was also added into the slip for providing a dispersion of slip and protecting the sedimentation of clay particles. Various concentrations of CMCp and commercial CMC (CMCc) (0.05, 0.1, 0.15, 0.2 and 0.25% w/w of dry weight of clays) were added into the slip. Effect of CMC on viscosity of the slip and the ceramic density were studied. The relationship between the ceramic properties such as, shrinkage, porosity, casting rate and bending strength (both green strength and fired strength), and CMC concentration was also observed. As increasing both CMCp and CMCc, viscosity increased while density decreased. The prepared ceramics (green ware and fired ware) added with CMCp were found to have higher strength and lower in %shrinkage than that of adding with CMCc. The thickness of the ceramic wall adding CMCc increased with increasing CMCc concentration, and time in contrast to that of CMCp as the thickness decreased with increasing CMCp concentration. However, the ceramics with addition of CMCp possessed higher strength than that of the commercial one. © (2010) Trans Tech Publications.